SPRED1 Is Downregulated and a Prognostic Biomarker in Adult Acute Myeloid Leukemia - Zhang, Rui; Zhang, Yan; Lu, Xianglan; Xu, Weihong; Wang, He; Mo, Wenbin; Pang, Hui; Tang, Rurong; Li, Shibo; Yan, Xiaojing; Li, Yan (Frontiers in Oncology, 2020)
We report herein that Sprouty-Related EVH1 Domain-Containing Protein1 (SPRED1) is downregulated and a prognostic biomarker in adult acute myeloid leukemia (AML). We determined mRNA levels of SPRED1 in the bone marrow mononuclear cells from adult patients, including 113 AMLs and 22 acute lymphoblastic leukemias (ALLs), as well as in 37 healthy control subjects. Significantly decreased SPRED1 mRNA expression was found in AML patients comparing to those in ALL patients and healthy controls, which was confirmed by immunocytochemistry analysis of SPRED1 protein and ELISA measurement of serum SPRED1 level. Further analysis demonstrated that SPRED1 expression was significantly higher for most patients at complete remission after induction treatment than at diagnosis. Moreover, SPRED1 expression was significantly downregulated in M2 and M3 types. Non-acute promyelocytic leukemia (non-APL) patients with decreased SPRED1 had significantly lower 2-year progression-free survival and event-free survival rates. In vitro, ectopic overexpression of SPRED1 leads to a decrease of extracellular signal-regulated kinase (ERK) phosphorylation, induction of apoptosis and reduction of proliferation of THP-1 cells. Our findings suggest SPRED1 is not only a predictor of treatment response, but also an independent prognostic factor for non-APL, and targeting Ras- Mitogen-activated protein kinase (MAPK) signaling may be a promising strategy for the treatment of AML with downregulation of SPRED1.